2013
DOI: 10.1099/vir.0.054395-0
|View full text |Cite
|
Sign up to set email alerts
|

An interaction between the methyltransferase and RNA dependent RNA polymerase domains of the West Nile virus NS5 protein

Abstract: The flavivirus nonstructural protein 5 (NS5) is a large protein that is structurally conserved among members of the genus, making it an attractive target for antiviral drug development. The protein contains a methyltransferase (MTase) domain and an RNA dependent RNA polymerase (POL) domain. Previous studies with dengue viruses have identified a genetic interaction between residues 46-49 in the aA3-motif in the MTase and residue 512 in POL. These genetic interactions are consistent with structural modelling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Genetic interaction between NS5-MTase and NS5-Pol has been reported for DENV ( 21 ) and WNV ( 22 ). In addition, the interaction between recombinant WNV NS5-MTase and NS5-Pol was demonstrated in vitro ( 23 ). The NS5-Pol domain was shown to enhance the internal RNA methylation activity of the NS5-MTase domain in the context of the full-length NS5 proteins of DENV and WNV ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic interaction between NS5-MTase and NS5-Pol has been reported for DENV ( 21 ) and WNV ( 22 ). In addition, the interaction between recombinant WNV NS5-MTase and NS5-Pol was demonstrated in vitro ( 23 ). The NS5-Pol domain was shown to enhance the internal RNA methylation activity of the NS5-MTase domain in the context of the full-length NS5 proteins of DENV and WNV ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier crystal structures of NS5 individual domains suggested that the evolutionarily conserved R262, whose guanidinium group hydrogen bonds with the main chain carbonyl oxygen of V97, defines the C terminus of the MTase domain ( Fig. 1C ; S3 Fig in S1 Text ) [ 1 , 28 , 32 , 57 , 60 ]. Residues H263-V264-N265-A266, which are located after the C-terminal end of the MTase domain, are the least evolutionarily conserved in the interface region ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, substitution of amino acids 46, 47 and 49 in the αA3 motif of the MTase in a dengue infectious clone severely reduced virus replication but this mutant was rescued by a spontaneous second site mutation at amino acid 512 in the palm of the RdRP suggesting intra-domain interaction between these residues [177]. However, although co-expressed WNV MTase and RdRp domains could be co-immunoprecipitated confirming interactions between these domains, none of the αA3 mutations affected the efficiency of the MTase-RdRp interaction [182]. In the structure of the full length Japanese encephalitis virus NS5, the MTase domain was found to interact with the backside of the RdRp domain and to only partially cover the top-right corner of the NTP entry channel instead of being located close to the dsRNA channel as previously predicted [181].…”
Section: Viral Nonstructural Proteinsmentioning
confidence: 99%